Procedural fairness for radiotherapy priority setting in a low resource context. (20th August 2021) - DeBoer, Rebecca J.; Nguyen, Cam; Mutoniwase, Espérance; Ho, Anita; Umutesi, Grace; Bigirimana, Jean Bosco; Triedman, Scott A.; Shyirambere, Cyprien
Abstract: Radiotherapy is an essential component of cancer treatment, yet many countries do not have adequate capacity to serve their populations. This mismatch between demand and supply creates the need for priority setting. There is no widely accepted system to guide patient prioritization for radiotherapy in a low resource context. In the absence of consensus on allocation principles, fair procedures for priority setting should be established. Research is needed to understand what elements of procedural fairness are important to decision makers in diverse settings, assess the feasibility of implementing fair procedures for priority setting in low resource contexts, and improve these processes. This study presents the views of decision makers engaged in everyday radiotherapy priority setting at a cancer center in Rwanda. Semi‐structured interviews with 22 oncology physicians, nurses, program leaders, and advisors were conducted. Participants evaluated actual radiotherapy priority setting procedures at the program (meso) and patient (micro) levels, reporting facilitators, barriers, and recommendations. We discuss our findings in relation to the leading Accountability for Reasonableness (AFR) framework. Participants emphasized procedural elements that facilitate adherence to normative principles, such as objective criteria that maximize lives saved. They ascribed fairness to AFR's substantive requirement of relevance more than transparency, appeals, and enforcement. They identified several challenges unresolved by AFR, such as conflicting relevant rationales and unintended consequences of publicity and appeals. Implementing fair procedure itself is resource intensive, a paradox that calls for innovative, context‐appropriate solutions. Finally, socioeconomic and structural barriers to care that undermine procedural fairness must be addressed.